Enhanced Superconducting Gap in the Outer CuO_{2} Plane of the Trilayer Cuprate (Hg, Re)Ba_{2}Ca_{2}Cu_{3}O_{8+δ} - Horio, M.; Miyamoto, M.; Mino, Y.; Ishida, S.; Thiagarajan, B.; Polley, C. M.; Lee, C. H.; Nishio, T.; Eisaki, H.; Matsuda, I. (Physical Review Letters, 2025)
We report the first observation of a momentum-resolved superconducting gap in the Hg-based trilayer cuprate, which holds the highest record of superconducting transition temperature (T_{c}) at ambient pressure. By angle-resolved photoemission spectroscopy utilizing a microfocused beam, clear quasiparticle dispersions originating from the inner and outer CuO_{2} planes (IP and OP, respectively) were separately identified. The magnitude of the superconducting gap for the IP was comparable to that of the Bi-based trilayer cuprate with a lower T_{c}. In contrast, the superconducting gap for the OP was significantly larger than that of the Bi-based one. While strong pairing in the IP has been highlighted as the key element of trilayer cuprates, the present results suggest that the enhanced pairing energy in the OP is essential for the highest T_{c} at ambient pressure realized in the Hg-based trilayer cuprate.